Self-Empowerment: Between Work Motivation, Time Management, and Responsibilities as a Student - Jihan Nuza Sabrina; Andriyastuti Suratman (Cita konsultindo, 2025)
This research aims to examine Self-Empowerment: Between Work Motivation, Time Management, and Responsibilities as a Student. The respondents in this study consisted of 11 university students who work part-time in Yogyakarta. The sampling technique used was purposive sampling, with criteria requiring respondents to be part-time students who have been working for at least three months. Data collection was conducted through interviews with respondents selected based on their relevance to the research objectives. The challenges faced by part-time student workers include time management, as they must balance dual roles as both students and employees. In addition, part-time student workers often experience stress due to workload or the dual roles they must perform. The findings of this study reveal that the participants generally have a positive self-evaluation regarding their performance, demonstrate a strong commitment to continuous growth, and successfully apply adaptive time management strategies and stress management techniques to cope with their dual responsibilities. It is recommended that companies provide adequate rest time and fair, transparent incentives for part-time workers. Future research is suggested to employ quantitative methods to measure the extent of the influence of work motivation, time management, and work stress variables on employee performance.